Turan's inequality for appell polynomials. (3rd January 2006) - Simic, Slavko
Abstract : We give some necessary and sufficient conditions for the class of Appell polynomials to satisfy well-known Turan's inequality. Among the other corollaries, we apply our results to some classes of orthogonal polynomials.